International personal data transmission European Union approach - Gültekin Várkonyi Gizem; Jog határok nélkül (2017) (Szeged) (2018)
Transmission of the personal data outside of the national jurisdiction has always been a debate at the international level. It is because, for instance, online service providers that offer their services based on personal data can be located in different countries or growing security threats make the personal data necessary to be a part of an intelligence that should be shared with other countries for the world peace. On the other hand, different understanding of privacy between the countries may cause breach of personal data protection right. Some of the data transmission conflicts between the United States and the European Union regarding to transmission of the personal data could be solved with bilateral agreements and they became a model for the EU for further collaborations with the third countries.
Keywords: Társadalomtudományok; Jogtudomány